Optimization Analysis of Switch Numbering in Metro Power Supply System - WANG Xiaobo; CHANG Hang (Chengshi guidao jiaotong yanjiu)
［Objective］ With the continuous improvement of metro network, the names of switches in the power supply system at all levels can no longer accurately mark the systems they belong to, meanwhile the duplicated and insufficient numbering also occur. Therefore, it is necessary to optimize the switch numbering in metro power supply system. ［Method］ The current situation of switch numbering scheme for the power supply system in Xi’an Metro, for example, is evaluated. Compared with the power supply systems for metros, electrified railways and the State Grid in other cities of China, the problems existing in the scheme are analyzed and specific solutions proposed. Starting from the characteristics of the power supply system switch numbers, considering their uniqueness and relevance, and combined with the planning of metro lines, the power supply system switch numbers are optimized and a new numbering method is proposed based on an analysis of its feasibility. ［Result & Conclusion］ The optimized switch numbering scheme for metro power supply system largely solves the numbering problems such as duplicate, disorder, poor organization and regularity. At the same time, it also realizes feeder and busbar classification, and voltage level identification, ensuring the uniqueness of the equipment names and numbers within each network area.